Constantine, a framework for narration in the contemporary Algerian novel - Cheribet, Khadidja (Journal of Human Sciences, 2022)
Constantine is a framework of narrative, which means that the narrative and its course are subject to a special space that characterizes the city as a geographical range, over which a group of people lives under a set of city customs, framed by a unique urban and urban structure stemming from community’s originality, heritage and future aspirations that are open to the stakes of the present. Some novels have attempted to present the city of Constantine TO readers as a visual structure, as well as as a set of perspective with vision of the conditions of this ancient city.